Modernizing Shibboleth IdP Server Using Ansible Automation to Enhance Crisis Management in a University Environment - Kosíková, Eliška (2024)
Following thesis aims to modernize the Shibboleth Identity Provider server infrastructure at the Prague University of Economics and Business by implementing Ansible automation. The primary business goal is to enhance the efficiency and reliability of the university’s Linux server deployment processes, improve disaster recovery capabilities, and optimize overall server administration and management. The thesis begins with an analysis of the current state of authentication servers at the university, highlighting the limitations of manual server deployment and upgrades, which lacked standardized procedures and documentation. This approach resulted in inefficient workflows, consuming considerable time and resources. This thesis further explores the role of Ansible in server and application deployment and management and identifies areas that could benefit from automation. It also examines how documentation is used as a code. Additionally, the thesis details the creation of new Ansible roles designed to automate Shibboleth Identity Provider server deployment tasks. It explains their implementation, evaluates their effectiveness, and demonstrates how the solution contributes to the optimization of server management at the university.